Investment Pattern Javanese Tribe Employees in TV One at Pulogadung Office Based On Ethnographic Approach - Putra Jaya, Hamka; Soviatun, Nuria; Akhsan, Lurinjani; Heikal, Jerry (CV. Publikasi Indonesia, 2022)
Investment is one way to manage finances in order to earn more income than before. Many people realize how important it is to invest early. Investments that can also be called investments to obtain returns have many types. Each type of investment instrument has its own benefits. In addition, each type also has its own advantages and disadvantages. This study aims to determine the investment patterns of Javanese employees in the TV One Pulogadung office. This study uses qualitative techniques using an ethnographic approach. The author conducted direct interviews with 10 employees of TV One Pulogadung who are ethnic Javanese. Based on the research results, there were 47 coding, 12 categories and 2 themes, namely asset investment and business investment. Based on the results of the study, it was concluded that Javanese employees at the TV One Pulogadung office prefer asset investment, especially land and buildings. This is in accordance with the Javanese culture which considers land to have a very important or sacred meaning. This is in accordance with the Javanese philosophy which reads